Student learning motivation on Actionbound application implementation in construction and building utilities subject - Rosdiana, A F; Busono, R R T; Yosita, L (IOP conference series. Materials Science and Engineering, 2020)
The research aimed to determine the students' learning motivations on Actionbound application implementation as learning media in construction and building utilities subject. This research was grounded by monotonous and boring learning media, so the researcher tried to innovate the learning media used Actionbound application to make students more interested to take class. This research was conducted by 30 second grade students of modelling design and building information program in SMKN 2 Garut, with Research and Development as research method. The data collection was carried out by media assessment sheets, learning motivations questionnaires, and student response questionnaires. Media assessed by expert judgement was considered very suitable to use. The students' media responses considered by media content, media language, strategy effect, and media visual had very good responses. The self-efficacy, active learning strategies, learning value, performance goal, achievement goal, learning environment stimulation, as learning motivation aspects showed a "high" category value. Therefore, the developed Actionbound application is suitable for use as learning media in construction and building utilities subject in SMKN 2 Garut.